Tabung Seri Kenyalang / Khairul Anwar Saadi - Saadi, Khairul Anwar (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
"Tabung Seri Kenyalang: Empowering Future Graduates" In conjunction with the 96th UiTM Convocation Ceremony, UiTM Sarawak introduced the "Tabung Seri Kenyalang" (TSK) fund. Established in 2018, TSK aims to assist (B40) Bumiputera students in need by providing financial support for tuition fees, living expenses, allowance for industrial training and even aiding in times of misfortune such as accidents or natural disasters.